The Signified and Signifier of Trauma and Identification—A Case Studies of Mom’s Trauma in Amos Oz’s a Tale of Love and Darkness - Wu , Yun (Journal of Theory and Practice of Contemporary Education, 2023)
Though the signified and the signifier are the linguistic terms, they garner great significance in literature which sheds great light on the connotation of the concept in literary works, such as trauma and identification. To the majority of Jews, trauma has the historical root in their mind which haunts everyone, particularly to women. Amos Oz who is regarded as most prolific writer in Israel kept portraying Jewish wish of identification and Zionism. However, the road to fulfil the wish turned out to be more like a disillusionment which deepens the trauma of Jews. The thesis is going to explore the trauma of Fania in A Tale of Love and Darkness so as to better apprehend the trauma suffered by Jews from the perspective of the signified and the signifier.